Associations of posttraumatic stress disorder symptoms with amyloid burden in cognitively normal older adults - Zhang, Lei; Gong, Yi-Miao; Wang, San-Wang; Shi, Pei-Ling; Li, Ming-Zhe; Wen, Xin; Wang, Di-Xin; Zheng, Yong-Bo; Han, Yong (Frontiers in Aging Neuroscience, 2024)
BackgroundPosttraumatic stress disorder (PTSD) is associated with the development of dementia. However, the link between PTSD and preclinical Alzheimer’s disease pathology (amyloid β [Aβ]) remains controversial. Moreover, the correlation between the severity of PTSD with Aβ levels remains unknown.MethodsThis cross-sectional study sought to investigate the associations of PTSD symptoms with global and regional brain Aβ burden. To this end, data were obtained from participants in the Anti-Amyloid Treatment in Asymptomatic Alzheimer’s Disease (A4) Study. In addition, we explored the association between the severity of PTSD symptoms and Aβ levels.ResultsA total of 4,228 participants aged 65 to 85 years were included in the final analysis. The results showed that PTSD symptoms were significantly associated with higher global Aβ levels (1.15 ± 0.20 vs. 1.09 ± 0.19; β = 0.056; p < 0.001), after adjusting for covariates. The association between PTSD symptoms and Aβ levels was not affected by sex, age, ApoE genotype, or psychiatric diseases. Similarly, PTSD symptoms were significantly associated with Aβ levels in all subregions, including the anterior cingulate, posterior cingulate, parietal cortex, precuneus, temporal cortex, and frontal cortex. In addition, the group with severe PTSD symptoms (1.22 ± 0.24) exhibited higher global Aβ levels than the groups with moderate (1.14 ± 0.19) or mild (1.12 ± 0.20) symptoms or the control (1.08 ± 0.18), with p < 0.001.ConclusionThe findings imply a close relationship between PTSD and brain Aβ levels, irrespective of sex, age, ApoE genotype, or psychiatric diseases. More well-designed studies are needed to further explore the relationship and mechanism underlying the association between PTSD and Aβ burden.